A Functional for Copulas and Quasi-Copulas. (3rd May 2012) - Úbeda-Flores, Manuel
Abstract : We recall and study some properties of a known functional operating on the set of n -copulas and determine conditions under such functional is well defined on the set of n -quasi-copulas. As a consequence, new families of copulas and quasi-copulas are defined, illustrating our results with several examples.